EFEKTIVITAS INOVASI PENGELOLAAN SUNGAI DAN PENATAAN SANITASI SEBAGAI KONSEP SUSTAINABLE DEVELOPMENT DALAM PENANGANAN MASALAH PERKOTAAN DI PROBOLINGGO - astutik, murtias puji; Aisyah, Rizaa; Maulina, Renanda; Rachman, Dinda; Hasanah, Zairotul (Publicio: Jurnal Ilmiah Politik, Kebijakan dan Sosial, 2022)
Sanitation and river management have become issues that have not been resolved lately because considering the growth and development of such population in the City or Regency is a problem that sounds very complete. This sanitation program is motivated to avoid a disease that causes death. So, the implementation of clean living is more encouraged considering that the City of Probolinggo is prone to flooding. This research will explain how a program to make river sanitation and management in the City of Probolinggo become more focused and orderly by implementing development and participation in the local community or residents. By using qualitative research methods and the descriptive approach used is the unit of analysis in the form of the concept of community-based development to determine the local socio-cultural conditions by paying attention to the values in the community. Keywords: River Management, Sustainable Development, Sanitation